2018
DOI: 10.1093/jcag/gwy050
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inflammatory Bowel Disease in Canada 2018: Indirect Costs of IBD Care

Abstract: The indirect cost of illness represents the portion of human capital that is foregone due to lost productivity of patients and their caregivers and out-of-pocket healthcare expenses borne directly by patients. Indirect costs among persons with inflammatory bowel diseases (IBD) may be substantial because disease onset occurs during the teens and 20s for most persons and is lifelong. Thus, most persons with IBD are affected during periods of study or employment. The literature on indirect health-related costs am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 50 publications
(51 reference statements)
0
27
0
1
Order By: Relevance
“…To what extent this difference also results in future lost life chances (eg not as good educational results and less well‐paid employments as would have been expected) and reduction in lifetime earnings is yet to be shown. More importantly, many studies have also shown that patients with IBD, regardless of age of diagnosis, have more work loss (sick leave and disability pension) than matched reference individuals or IBD‐free siblings 4‐9 ; these observations to us suggests that it is the disease itself, with its remitting and relapsing disease course, rather than the (limited) reduction in adult height that causes reduced lifetime earnings. That is, if lifetime earnings are indeed reduced, which is yet to be shown (although we agree it is likely).…”
mentioning
confidence: 76%
“…To what extent this difference also results in future lost life chances (eg not as good educational results and less well‐paid employments as would have been expected) and reduction in lifetime earnings is yet to be shown. More importantly, many studies have also shown that patients with IBD, regardless of age of diagnosis, have more work loss (sick leave and disability pension) than matched reference individuals or IBD‐free siblings 4‐9 ; these observations to us suggests that it is the disease itself, with its remitting and relapsing disease course, rather than the (limited) reduction in adult height that causes reduced lifetime earnings. That is, if lifetime earnings are indeed reduced, which is yet to be shown (although we agree it is likely).…”
mentioning
confidence: 76%
“…The total financial burden of IBD in the United States was estimated to be US $14.6 billion to US $31.6 billion in 2014 [ 6 ]; however, recent data have indicated that the total costs may far exceed these earlier estimates [ 7 ]. In Canada, wherein the prevalence of IBD is one of the highest in the world, the economic cost for IBD was conservatively estimated to be over US $0.9 billion in 2018 [ 8 ]. In Europe, 2.5-3 million people have been estimated to be affected with IBD with a direct health care cost of 4.6-5.6 billion Euros/year [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1] It has a higher incidence in Canada and reports of more difficult treatments. [2][3][4] Clinically, this type of patients has a slow treatment effect and a long treatment period, which have attracted the attention of gastrointestinal physicians and need expensive costs [4] . The disease is considered a patient's immune system disorder, and changes in the intestinal flora and its metabolites usually affect the patient's immune system, thereby inducing the disease.…”
Section: Introductionmentioning
confidence: 99%